Development Device Learning Differentiated with Use PJBL Method on Material Get up Flat - Juan Gabriel Mongkau; Juliana Margareta Sumilat; Richard DH Pangkey (International Journal of Educational Evaluation and Policy Analysis, 2025)
This research aims to develop a mathematics teaching module based on differentiated learning integrated with the Project-Based Learning (PjBL) method, specifically for the topic of spatial structures ("get up room") for students at Nanasi 1 Elementary School. The development process follows the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. In the Define stage, analysis revealed the absence of instructional modules that align with students' learning styles and needs. Consequently, learning objectives were formulated based on geometric elements and problem-solving criteria. During the Design stage, a prototype module and validation instruments were produced. Validation was conducted by two experts, yielding high scores for both content and visual presentation—each achieving 90% validity. Practicality assessments also showed strong results, with content rated at 90.8% and visual aspects at 90%, categorizing the module as “very valid” and “very practical.” The integration of the PjBL method was implemented to enhance active student participation, encouraging collaborative exploration and real-world application of mathematical concepts. The developed module is considered suitable for supporting differentiated mathematics instruction in elementary schools. It accommodates diverse learning styles and promotes student engagement through project-based tasks. The findings suggest that combining differentiated learning with PjBL fosters a more inclusive and effective learning environment, particularly in geometry-related topics. This module not only meets pedagogical standards but also contributes to the advancement of innovative teaching practices in primary education.